Pemahaman PetaniTentang Budidaya Kopi Arabika dan Pengaruhnya Terhadap Produktivitas Hasil Panen - I Komang Agus Suara; I Wayan Widia; Ida Bagus Putu Gunadnya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2018)
The aims of this study were to determine the level of understanding of farmers on coffee cultivation and its effect on productivity. Observed cultivation aspects included land preparation, light intensity regulation, planting techniques, plant breeding, fertilizer application, pest control, plant rejuvenation, and coffee harvesting. The research involved 45 respondents selected using simple random sampling from coffee member farmers of MPIG Kintamani, Bali. The highest value among research variables was obtained in plant rejuvenation, while the lowest was in coffee harvesting. Data analysis using Confirmatory Factor Analysis (CFA) and Multiple Regression Analysis (MRA) showed three cultivation factors significantly contributing to crop productivity: land preparation, planting techniques, and plant rejuvenation. Land preparation and planting techniques had a positive effect on Arabica coffee productivity, whereas plant rejuvenation had a negative effect. Planting techniques had the most dominant influence on Arabica coffee productivity. It is expected that these findings can help improve Arabica coffee production in Bali, currently at 0.5 tons per hectare, thereby contributing to national coffee production.